Diversity and zonation of mangrove flora in Belitung Island, Indonesia - Afri Irawan; Tatik Chikmawati; Sulistijorini SULISTIJORINI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Irawan A, Chikmawati T, Sulistijorini. 2021. Diversity and zonation of mangrove flora in Belitung Island, Indonesia. Biodiversitas 22: 2981-2992. Mangrove is an important ecosystem located in the coastal tidal zone in tropical and sub-tropical regions. This ecosystem is characterized by the presence of plant species that can survive in brackish and inundated zone of seawater. There are many mangrove forests in Belitung Island, Indonesia, but the data of mangrove flora diversity and zonation in this island have not been described. This study aims to reveal the diversity and analyze the zonation of mangrove flora in Belitung Island. This research was conducted using a cruising method to explore the diversity of mangrove flora species and a line transect to analyze the zonation of mangrove flora. The exploration locations for diversity of mangrove flora were Kuale Tambak Beach, Asam Beach, Belitung Mangrove Park Area, Manggar River, Sentigi Beach, Sabong Beach, and Kembiri Beach. Mangrove flora zonation was observed in Asam Beach (north), Kembiri Beach (south), and Kuale Tambak Beach (east). The result showed that mangrove flora in Belitung Island consisted of 12 families, 16 genera, and 24 species. Species found were dominated by 8 species from the Rhizophoraceae family with the largest number of species were from the genera of Bruguiera and Rhizophora. The species of Bruguiera included Bruguiera gymnorhiza, Bruguiera sexangula, Bruguiera cylindrica and Bruguiera parviflora. Meanwhile, the Rhizophora species that have been found were Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa. The Kembiri beach had the highest number of species of the mangrove flora with 18 species. The zonation of mangrove flora at each research location showed a different zonation pattern. The mangrove vegetation on Kulae Tambak Beach was behind the Casuarina equisetifolia vegetation, while the mangrove vegetation on the Asam and Kembiri Beaches directly faced the sea. The difference in zonation patterns is likely caused by local topography on Belitung Island, substrate conditions and salinity factors on the mangroves of Belitung Island